Analysis to The Policy of Delaying The Execution of Those Sentenced to Death is a Violation of Human Rights - Muhaimin Muhaimin (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
Human rights are basic rights of the human being that exist and are a gift of Almighty God. Human rights are also natural rights that therefore cannot be revoked by other human beings. Indonesia is one of the countries that still apply the death penalty in its positive law where the unlawful acts are considered an extraordinary crime that endangers the lives of the nation and the State. The discourse of Indonesia as a country that has the philosophy of Pancasila until now can cause pro and con problems, because there are still many among legal experts and human rights activists as well as the public who question it because of differences and views, among others. The statement of the problem in this scientific paper is “How is the policy related to the death penalty in human rights seen from the current positive legal regulations?” The method used in this study is a normative juridical method. Seeing so many convicts with sentenced to death who have not been executed, it can be said that the State has committed human rights crimes (against convicts with sentenced to death), because they have served the sentence for the 2nd (second) time, namely the Imprisonment and Death Penalty. The implementation of Restorative Justice is possible to be executed as a legal breakthrough, where it becomes a solution to avoid human rights violations that can occur within the time of the delay of the death penalty. The National Commission for Human Rights (the Komnas HAM) as a representative of the Government is expected to be more aggressive in protection efforts.